PENGAWASAN SATUAN POLISI PAMONG PRAJA DALAM MEWUJUDKAN PENATAAN RUANG DARI BANGUNAN LIAR DI KABUPATEN KARO - Jannus T.H, Siahaan; Mirnawati Br. Barus (JURNAL GOVERNANCE OPINION, 2021)
This study aims at finding out how the Supervision has been carried out by the Civil Service Police Unit in realizing the Spatial Planning of Illegal Buildings in Karo Regency and to find out whether the Supervision of Illegal Buildings in Karo Regency has been carried out by the Civil Service Police Unit to the maximum. The research method used by the researcher is a qualitative research that produces and processes descriptive data, such as interview transcripts, field notes, pictures, photos, video recordings, and others. Thus, the researcher tried to dig up information by interviewing several people involved in the research, namely: the Head of the Karo District Pamong Praja Police Unit, the Karo District Head of Public Order Unit and the Karo District Pamong Praja Police Unit Supervision Unit Head. The Civil Service Police Unit had a fixed procedure (protap) supervision in realizing spatial planning of illegal buildings in Karo Regency. Regional Regulations and Regent Regulations are the main reference in conducting supervision. The Karo District Civil Service Police Unit has carried out maximum surveillance of illegal buildings. They carry out socialization before taking firm action regarding illegal buildings. Then after receiving public complaints, a warning letter is issued, and if within 14 days it is not heeded, demolition is carried out.